We are fighting for the liberation of our people: Justifications of violence by activist youth in Diepkloof, Soweto - Marks, Monique (My University, 1995)
This paper, which seeks to understand youths' own justifications for engaging in acts of collective violence, is based on a case study of activist youth and their organisations in Diepkloof, Soweto. The research was conducted during the period 1991 - 1993. While the specificities and peculiarities of any particular area make generalisations difficult, many of the conditions under which Diepkloof youth live, as well as their experiences, are probably very similar to those of youth in other townships in Soweto, the Gauteng province, and indeed, South Africa. Consequently, while the research claims to give insight into the consciousness of activist youth in Diepkloof, some of these findings may be applicable to youth in other townships.
African Studies Seminar series. Paper presented 28 August 1995
Keywords: Student movements. South Africa. Soweto; National liberation movements. South Africa. Soweto; Violence. South Africa. Soweto; Young adults. Political activity; Youth. Political activity